Sephardi Archives and Virtual Encounters in Esther Bendahan Cohen's Fiction. - Cohn, Adam (Hispanófila)
This article explores the confluence of archives, Spanish-Jewish encounters, and modern technology in the narrative fiction of Spanish-Moroccan writer Esther Bendahan Cohen. The analysis of Soñar con Hispania (2002, co-authored with Ester Benari), Déjalo, ya volveremos (2006), and the short story "Popey" from Una hora solamente, de la orilla del día (2016) considers how these texts simulate archives or perform an archival function in response to concerns about documenting and remembering Sephardi history. All three texts employ a dialogical model of memory in which pairs of characters engage with or imagine the Sephardi past, whether through historical research in Soñar con Hispania or the fake passport game in Déjalo, ya volveremos. Reimagining the 19th-century trope of the Spanish-Jewish encounter in a modern key, her fiction also makes use of the opportunities that the Internet provides for interactions between both groups. Framed as an online chat exchange, "Popey" offers a playful take on the Spanish-Jewish love plot that turns to the archive as a source of legitimization in an otherwise indeterminate story. Ultimately, Bendahan Cohen's fiction reclaims and creates archives as a self-empowering act that renders Jewish experiences visible in contemporary Spain.